1981
DOI: 10.1113/jphysiol.1981.sp013581
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties and myosin light chain composition of skinned muscle fibres from adult and new‐born rabbits.

Abstract: 1. The maximum velocity of shortening, Vmax, and stiffness were measured in skinned single fibre segments from psoas and soleus muscles of adult rabbits and psoas muscles of new‐born rabbits, and the myosin light chain composition was also determined in the same segments used in the mechanical studies. 2. Vmax was obtained at 15 degrees C during maximal activation at pCa 5.49 using a method involving measurement of the time required to take up various amounts of slack imposed on the segments. Stiffness was mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
1

Year Published

1981
1981
2010
2010

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 46 publications
5
21
1
Order By: Relevance
“…Tre of fibres in rigor was much greater than that found with our earlier preparative technique (Tregear, 1988) and was comparable to the value found in isometric contraction [Tre of 650 ~N (Table 1) in a 75 ~m fibre implies 150 kN m-2; Julian et al (1981) obtained 160kN m -2 from isometrically-activated rabbit psoas at 15~…”
Section: Tension During Stretchsupporting
confidence: 83%
“…Tre of fibres in rigor was much greater than that found with our earlier preparative technique (Tregear, 1988) and was comparable to the value found in isometric contraction [Tre of 650 ~N (Table 1) in a 75 ~m fibre implies 150 kN m-2; Julian et al (1981) obtained 160kN m -2 from isometrically-activated rabbit psoas at 15~…”
Section: Tension During Stretchsupporting
confidence: 83%
“…A number of studies on single fibres from mammalian and amphibian skeletal muscle showed that differences in MHCs but hot MLCs correlate with shortening velocity (Julian et al, 1981;Reiser et al, 1985;Lannergren, 1987). For instance, in the fast fibres of Xenopus skeletal muscle no significant correlation has been found between shortening velocity and the relative proportions of the two alkali light chains (Lannergren, 1987).…”
Section: Discussionmentioning
confidence: 95%
“…In addition, failure to identify the high-velocity phase of shortening would give rise to an over-estimate of the extension of series elements during tension development at low levels of activating Ca2+. Since the ordinal intercept of the straight line fitted to slack-test data is a measure of the extension of series elements (see Julian, Moss & Waller, 1981), lines fitted only to data in the low-velocity phase of shortening will yield an apparent and paradoxically greater extension of series elements (such as connexions to the apparatus) at low Ca2+ concentrations than at high (see Moss, 1982).…”
Section: Discussionmentioning
confidence: 99%